The golden bird : folk tales from Slovenia - Kavcic, Vladimir, 1932-; Gerhard, Mae (London : MacDonald, 1969)
Eighteen tales from Slovenia, now a part of Yugoslavia, tell of clever and magical animals, beautiful princesses, brave princes, ogres, and demons
Keywords: Tales -- Yugoslavia -- Slovenia